Studi Kelayakan Bisnis Internet dan Games di Kota Manado - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
Warnet (warung internet) still unable to fulfill and serve the need of information service through faster internet connection, provide wider and flat computer screen, air conditioned rooms supported by other facilities such as cafe, games online and LAN, able to access journals, books, magazine and watching seminar online. For community of Manado city, the prospect of doing warnet business is profitable for investor.